The influence of the emission of energy from urban areas and communication routes on changes in the development of their surrounding ecosystems - Kaźmierczak, Urszula; Kulczycki, Andrzej (Studia Ecologiae et Bioethicae, 2012)
This article aims to draw attention to the hitherto unexplored and scarcely noticed the problem of the effects of the consumption of increasing amounts of energy to human health and ecosystems exposed to emissions processed in the phase of energy consumption. Ever-increasing amounts of energy are consumed in relatively small urban areas, in communication routes, and in airport areas. As far as Poland is concerned, these areas represent less than 10% of the country. For such a small area the energy consumed is converted to other forms of energy, much of which is emitted into the environment. These emissions primarily include heat and various forms of mechanical energy, mainly that of acoustic waves. It studies the effect of noise on the health of people living in the vicinity of highways, as well as studies of ecosystems in the surrounding routes. There is still no explanation for the reasons for this phenomenon, as research in this area has been mainly carried out at the level of statistical analysis. The article has pointed out the possible causes of this phenomenon. The new theory of catalysis demonstrates the effect of mechanical energy input on the direction and rate of chemical reactions. This effect can also be significant in the case of biochemical reactions. Finally, the paper points out the need and direction of research, conducted at various levels, to determine and explain the environmental effects of increasing energy consumption, other than the greenhouse one.